Rozmowa o wierze chrześcijańskiej dzisiaj - Witko, Krzysztof (Studia Pastoralne, 2020)
This article is about proclaiming the faith of the Church in the modern world in a pastoral and theological perspective. The starting point is a discourse combining the living tradition of the Church and the communal and personal experience of Christian faith. The second point presents the content and structure of the apostolic kerygma, showing its ecclesial background and paschal source. Finally, in the third point, the dialogue between Christian faith and the modern world was emphasized. We are talking here about the soteriological and eschatological perspective of the presence of the Church in the world, which, genetically speaking, comes from theological reflection on the basic mysteries of the Christian faith: the Incarnation, Redemption and Resurrection. The consequence of this approach to the problem is the postulate that the Christian message must be sensitive to the challenges of the present time, and at the same time deeply rooted in the Paschal experience of the Church’s faith and practice.